Gintonin Enhances Proliferation, Late Stage Differentiation, and Cell Survival From Endoplasmic Reticulum Stress of Oligodendrocyte Lineage Cells - Mijan, Mohammad Al; Kim, Ji Young; Moon, So-Young; Choi, Sun-Hye; Nah, Seung-Yeol; Yang, Hyun-Jeong (Frontiers in Pharmacology, 2019)
Although evidence on myelin diseases is steadily accumulating, effective preventive or therapeutic strategies against them have not been established so far. Ginseng is well-known for its beneficial effects on health and diseases; however, detailed studies on ginseng’s effects on myelin-producing oligodendrocytes have not been performed yet. In this study, we investigated the function of gintonin—an active component of ginseng—on the proliferation, differentiation, and survival of oligodendrocyte lineage cells. We performed real-time PCR, western blot, and immunocytochemistry on primary oligodendrocyte precursor cell cultures and in vitro myelinating co-cultures. Our results show that gintonin stimulates oligodendrocyte precursor cell proliferation. Gintonin’s effect was inhibited by Ki16425, an antagonist of lysophosphatidic acid 1/3 receptors. Interestingly, with regard to cell differentiation, gintonin facilitated late differentiation of oligodendrocyte development, but not early differentiation. Moreover, it showed protective effects on oligodendrocyte lineage cells against endoplasmic reticulum stress–induced cell death, potentially by modulating unfolded protein responses. Our results suggest that gintonin is a potential therapeutic candidate in the treatment of myelin diseases.